Multidrug-resistant Escherichia coli isolated from canine faeces in a public park in Quito, Ecuador. (September 2019) - Ortega-Paredes, David; Haro, Marco; Leoro-Garzón, Paula; Barba, Pedro; Loaiza, Karen; Mora, Francisco; Fors, Martha; Vinueza-Burgos, Christian; Fernández-Moreira, Esteban
Highlights: Presence of MDR E. coli in canine feces from Ecuador. Presence of clinically relevant alleles of bla CTX-M, bla CMY and the gene mcr-1 . Older people are more conscious of collecting and disposing of dog's feces. Canine feces in public settings might be a sentinel to study resistance. Abstract: Objectives: This study focused on estimating the prevalence of extended-spectrum β-lactamases (ESBLs), plasmid-mediated AmpC β-lactamases, carbapenemases and MCR-1-producing Escherichia coli in canine faeces from a public park in Quito, Ecuador. Methods: Phenotypic and genotypic characterisation of E. coli isolated from 50 canine faecal samples recovered from a city park in Quito was performed. In addition, a multiple choice survey was conducted among 50 dog owners. Results: Of the 50 faecal samples, 20 (40.0%) presented E. coli resistant to ceftriaxone. Moreover, 23 E. coli isolates were recovered for further analysis. All of the isolates showed as multidrug-resistant (MDR) phenotype (resistant to three or more antibiotic families). Resistance to carbapenems, tigecycline and amikacin was not observed. No major clonal relatedness was observed among the resistant isolates. The ESBL genes bla CTX-M-15, bla CTX-M-55 and bla CTX-M-65 were the most common. Two isolates harboured the bla CMY-2 gene and one isolate harboured both mcr-1 and bla CTX-M-65. Statistical analysis showed that older people were more conscious of collecting and disposing of dog faeces than subjects aged <35 years ( P < 0.05). Conclusion: The finding of MDR E. coli in dog faeces in a city park in Ecuador illustrates the importance of analysing canine faeces in public settings (e.g. parks, playgrounds) as part of surveillance programmes for MDR E. coli . In addition, this research might be a sentinel sampling method to gain a better understanding of community sources of antibiotic-resistant Enterobacteriaceae at human–animal–environment interfaces.